O uso do grafite como ferramenta didática no ensino de arte para alunos do ensino médio na EEEP Joaquim Nogueira - Queiroz, Antônio Geovane Monteiro de (2024)
This is a research into Visual Art Teaching that focuses on the use of graffiti as a teaching tool in art classes for high school students at EEEP Joaquim Nogueira. It arises mobilized by the following guiding question: how can the language of graffiti be used in a didactic way to make art classes more attractive and effective in student learning? The general objective of this study is to develop among students, through the graffiti, a conception of Visual Arts as an important field of knowledge for their training, in professional, human and social aspects. For this, we used as a theoretical reference the works of Ana Mae Barbosa (2015) and Betty Edwards (2021), Ernst Gombrich (2013), in order to show the importance of art for human beings in different aspects, in addition to introducing graffiti as an important modality of contemporary art for teaching, through the studies of Celso Gitahy (2017) and Luiz Fernando Lazzarin (2007). As a methodological contribution, the studies and concepts of Barbosa (2014) on the Triangular Approach were important, with regard to the structuring of classes taught to students collaborating in the research. We also have as an important point the use of the Atlas Mnemosine concept by historian Aby Warburg (2015), in order to show participating subjects the possibility of working with references from the History of Art, through the use and practical application of graffiti. In this sense, we also operationalized the concepts of Visual Culture by Fernando Hernández (2000), which served as a bridge between the students' daily lives and the knowledge of Art History during the practices of this type of urban artistic modality. To collect data, we applied questionnaires, used a field diary and photographic and videographic records in the field. It is worth noting that the concepts of Visual Culture by Hernández (2000) and Survivor Image by Didi- Huberman (2013) were fundamental in carrying out the data analysis. As a result, we were successful in producing a graffiti mural inspired by works from the Renaissance period mixed with pop culture references brought by the students themselves, in addition to creating an educational product in the form of a catalog containing the graffiti created by collaborators. It was observed through the collection of data and reports from the participants that this experience contributed significantly to them, in the sense of giving them greater artistic and aesthetic knowledge, while they learned new artistic skills and gained greater knowledge about the History of Art. In addition, they achieved gains in personal and social aspects, as they increased their self- confidence and also developed greater ability to interact with other people and work in groups. All these results occurred in a pleasant, welcoming environment conducive to learning.